Detection of Amorphous Silica in Air-Oxidized Ti3SiC2 at 500-1000°C - Pang, W.; Low, It-Meng; Hanna, J. (Polskie Towarzystwo Ceramiczne, 2010)
In this paper we describe the use of secondary-ion mass spectrometry (SIMS) and nuclear magnetic resonance (NMR) to detect the existence of amorphous silica in Ti3SiC2 oxidised at 500-1000°C. The formation of an amorphous SiO2 layer and its growth in thickness with temperature was monitored using dynamic SIMS. A duplex structure with an outer layer of TiO2 and an inner mixture layer of SiO2 and TiO2 was observed. Results of NMR verify for the first time the direct evidence of amorphous silica formation during the oxidation of Ti3SiC2 at the temperature range 500-1000°C.